Inceptor facilitates acrosomal vesicle formation in spermatids and is required for male fertility - Bilekova, Sara; Garcia-Colomer, Balma; Cebrian-Serrano, Alberto; Schirge, Silvia; Krey, Karsten; Sterr, Michael; Kurth, Thomas; Hauck, Stefanie M.; Lickert, Heiko (Frontiers in Cell and Developmental Biology, 2023)
Spermatogenesis is a crucial biological process that enables the production of functional sperm, allowing for successful reproduction. Proper germ cell differentiation and maturation require tight regulation of hormonal signals, cellular signaling pathways, and cell biological processes. The acrosome is a lysosome-related organelle at the anterior of the sperm head that contains enzymes and receptors essential for egg-sperm recognition and fusion. Even though several factors crucial for acrosome biogenesis have been discovered, the precise molecular mechanism of pro-acrosomal vesicle formation and fusion is not yet known. In this study, we investigated the role of the insulin inhibitory receptor (inceptor) in acrosome formation. Inceptor is a single-pass transmembrane protein with similarities to mannose-6-phosphate receptors (M6PR). Inceptor knockout male mice are infertile due to malformations in the acrosome and defects in the nuclear shape of spermatozoa. We show that inceptor is expressed in early spermatids and mainly localizes to vesicles between the Golgi apparatus and acrosome. Here we show that inceptor is an essential factor in the intracellular transport of trans-Golgi network-derived vesicles which deliver acrosomal cargo in maturing spermatids. The absence of inceptor results in vesicle-fusion defects, acrosomal malformation, and male infertility. These findings support our hypothesis of inceptor as a universal lysosomal or lysosome-related organelle sorting receptor expressed in several secretory tissues.